Kualitas Pelayanan Bus Rapid Transit Trans Semarang - Nursalim Nursalim; Agus Windu Sancono (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Writing articles in this journal aims to describe the service quality of the Trans Semarang Bus Rapid Transit and its sub parameters which include descriptions tangibles, reliability, responsiveness, assurance, dan empaty. The writing method uses a qualitative descriptive approach. The data source is the primary source of Trans Semarang Bus Rapid Transit passengers and the secondary data source is documents at the Trans Semarang Bus Rapid Transit company. Collecting data by observation and interviews with a questionnaire as an instrument. The discussion on the level of service quality of the Trans Semarang Bus Rapid Transit uses an analysis of the average percentage value through the sum of the scores achieved divided by the expected score multiplied by 100 %. Determining whether the quality of Trans Semarang Bus Rapid Transit service is good or not by determining very good 0.00-24.99%, good 25-49.99%, not good 50-74.99% and bad 75-100%. The findings of the discussion of the results of the analysis are that the level of service quality for the Trans Semarang Bus Rapid Transit is very good and also for several sub-parameters tangibles, reliability, responsiveness, assurance, and empaty are all very good level. However, there are several dimensions of the five service quality parameters in the unfavorable category. The conclusion from the findings of the discussion of the analysis of the service quality of the Trans Semarang Bus Rapid Transit is very good in its management so that it can realize the satisfaction of the people of Semarang City and its surroundings.